Symbiotic bacteria associated with different species of Curculio (Coleoptera: Curculionidae) and their host plants - Liu, Yingshan; Ying, Yue; Li, Yan; Zhang, Wei; Shu, Jinping (Frontiers in Microbiology, 2025)
Bacteria often play important roles in the host adaptation of phytophagous insects. Beetles of the genus Curculio (Coleoptera: Curculionidae) include pest species that bore into the seeds of trees in the family Fagaceae and damage the cotyledons. At present, there are few studies of the taxonomic diversity and functional effects of symbiotic bacteria involved in changes in host ranges and host adaptation of Curculio. Here, we used 16S rRNA gene Illumina and metagenomic sequencing to compare the composition and functions of the bacterial communities of three species of host plants and several Curculio species combinations: Curculio bimaculatus feeding on Castanopsis sclerophylla, C. bimaculatus feeding on Castanopsis tibetana, and Curculio davidi feeding on Ca. tibetana. The host plants influenced the diversity of symbiotic bacteria, while the Curculio species influenced the community structure of the symbiotic bacteria. Functional predictions showed that symbiotic bacteria contributed to the metabolism of the hosts. However, consistent with the variation in bacteria, the major metabolism-related bacterial genera varied among the treatment groups. Comparisons of metabolic enzymes based on KEGG (Kyoto Encyclopedia of Genes and Genomes) annotation revealed differences in the enzymes involved in insect development and detoxification of plant secondary compounds among the three groups, and the patterns were influenced by the dominance of the Curculio species on the host plants. This study provides valuable insights into the possible role of symbiotic bacteria in Curculio as host insects.